2023
DOI: 10.1080/21645515.2023.2219577
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pandemics and disruptions to vaccination on infectious diseases epidemiology past and present

Abstract: Infectious diseases are a leading cause of morbidity and mortality worldwide with vaccines playing a critical role in preventing deaths. To better understand the impact of low vaccination rates and previous epidemics on infectious disease rates, and how these may help to understand the potential impacts of the current coronavirus disease 2019 (COVID-19) pandemic, a targeted literature review was conducted. Globally, studies suggest past suboptimal vaccine coverage has contributed to infectious disease outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…38 This phenomenon has garnered attention due to its adverse consequences, notably the reduction in vaccine coverage, leading to an increased vulnerability to outbreaks and epidemics of preventable diseases. 39 The current research is specifically focused on the general population in the Somali Region of Eastern Ethiopia, aiming to assess their willingness to accept This finding aligns closely with findings from studies conducted in the USA, where the willingness rate was 69%, 40 in China with a willingness rate of 63.28% 41 and in Japan, where the corresponding figure was 65.7%. 42 However, the current study on acceptance of COVID-19 vaccines shows a lower level, as indicated by a study conducted in 23 countries, revealing an average acceptance rate of 79.1%.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…38 This phenomenon has garnered attention due to its adverse consequences, notably the reduction in vaccine coverage, leading to an increased vulnerability to outbreaks and epidemics of preventable diseases. 39 The current research is specifically focused on the general population in the Somali Region of Eastern Ethiopia, aiming to assess their willingness to accept This finding aligns closely with findings from studies conducted in the USA, where the willingness rate was 69%, 40 in China with a willingness rate of 63.28% 41 and in Japan, where the corresponding figure was 65.7%. 42 However, the current study on acceptance of COVID-19 vaccines shows a lower level, as indicated by a study conducted in 23 countries, revealing an average acceptance rate of 79.1%.…”
Section: Discussionsupporting
confidence: 64%
“… 38 This phenomenon has garnered attention due to its adverse consequences, notably the reduction in vaccine coverage, leading to an increased vulnerability to outbreaks and epidemics of preventable diseases. 39 The current research is specifically focused on the general population in the Somali Region of Eastern Ethiopia, aiming to assess their willingness to accept a COVID-19 vaccine. By delving into the intricacies of vaccine acceptance within this particular demographic, the study seeks to unearth insights into the factors influencing attitudes towards vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the CDC recently reported that, 11 between 2020 and 2022, over 61 million doses of measles-containing vaccine were postponed or missed due to COVID-19-related delays, elevating the risk of larger outbreaks globally. A consequence of the erratic MMR vaccine uptake over the past two decades is that many countries are now failing to achieve the high population immunity required to interrupt transmission of the highly infectious measles virus 12 The risk of large outbreaks associated with low vaccine uptake is further compounded by growing anti-vaccine sentiments and “vaccine fatigue” 13 after the COVID-19 pandemic and the growth of displaced populations through wars and famine in many parts of the world.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the 2023 measles outbreak in South Africa was caused due to low coverage of measles vaccine [ 7 ]. Similarly, there was an outbreak of Polio in Cameroon due to low coverage of Oral Polio Vaccine (OPV) [ 8 ], low vaccine coverage has contributed to infectious disease outbreaks in vulnerable population [ 9 ]. Vaccine hesitancy also contributes to low vaccination coverage in many Africa countries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%